THE EFFECT OF PARENTAL DEMOGRAPHIC CHARACTERISTICS ON PARENTS’ PERCEPTION OF DAYCARE CENTER SERVICES QUALITY IN DUAL-INCOME FAMILY IN INDONESIA - Putri, Rezti Wandanuri; Famiola, Melia (Journal of Economic, Bussines and Accounting (COSTING), 2025)
As dual-income families become more common in Indonesia, working parents face increasing challenges in balancing work and caregiving responsibilities. This mixed-method study aims to analyze the extent to which parental demographic characteristics—specifically education level, family income, and marital status—affect parents’ perception of daycare quality that they are using. The study combines a survey of 267 daycare users with in-depth interviews to enrich and contextualize findings. The results show that education level significantly influence parents evaluation of daycare Workforce Quality, Curriculum & Pedagogy, Monitoring & Evaluation, and Governance & Funding. Meanwhile family income and marital status did not show any significant effect. The result show that parents with higher education attainment tend to score the daycare quality lower, meaning they evaluate it more critically. While Access & Participation is the only dimension that did not show any correlation with education. According to the interview it show that Access & Participation is universal needs for parents regarding their characterisics of background. Keywords: daycare quality, dual-earner family, daycare, parental demographics, education, marital status, Indonesia